STUDI PADATAN TERSUSPENSI DI PERAIRAN PULAU TOPANG KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Jewlaika, Lady; Mubarak, Mubarak; Nurrachmi, Irvina (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
This research was conducted in December 2013 located in the Topang Island Waters. Samples were analyzed in the Sea Chemical Laboratory of Marine Science Department of Fisheries and Marine Science Faculty of Riau University. The purpose of this study is to deter-mine the distribution patterns of suspended solids at the low tide to the high tide and the high tide to the low tide in the Topang Island Waters. This study used a survey method which con-sists of 22 stations, one station with 2 sampling was at low tide to the high tide and high tide to the low tide. The pattern of distribution of suspended solids in the Topang Island Waters is uneven, when low tide to the high tide the highest TSS content is in the southeast, south, southwest and northeast of Topang Island Waters and when the high tide to the low tide, the highest TSS content is in the southeast, south and northeast of Topang Island Waters. The highest content of TSS is 70-100 mg/l which is quite high and less precise as source of fishing activities, then the lowest TSS content is 30-60 mg/l were classified as normal and decent enough for fishing activities.